Influência da utilização de redes sociais no desenvolvimento de Perturbação Dismórfica Corporal em adolescentes portugueses - Duarte, Ema Loureiro (2024)
Body Dysmorphic Disorder is a psychiatric illness defined by an enduring preoccupation with perceived defects on the appearance of an individual. These flaws are often dismissible or insignificant for those who surround them. As an obsessive-compulsive disorder, body dysmorphic disorder is characterized by repetitive rituals, including repeated examinations of one's own body, attempts to camouflage aspects considered imperfect and avoidance of stimuli that generate negative feelings. This illness leads to constant distress and the disruption of all aspects of the individual’s life. It is associated with high rates of suicidal ideation, attempt and completed suicide, which motivates delving deeper into its triggering factors. The disorder leads to an excessive self-analysis and comparison with unrealistic standards. In fact, social media keeps unrealistic standards on display, by providing tools to mask natural features or make them more aesthetically pleasing. Social media use eases the development of Body Dysmorphic Disorder and feeds into it. Multiple investigations attest that social media usage increases the concern about one’s appearance and dissatisfaction towards the body. The impact of social media is undoubtedly amplified when the user is at a more vulnerable age like the adolescence. This stage is characterized by constant comparison with pairs and a volatile self-perception. Since the introduction of social media is increasingly early, it is important to reflect about and analyse the role it plays in the development of several disorders, such as anxiety, depressive and eating disorders or the object of study, body dysmorphic disorder. Lastly, it is important to note that an individual’s beauty ideal and their definition of a flawed self-image depends on numerous factors, such as age, gender, or sexual orientation. On this basis, it is worthy to assess whether there are individuals who, due to their characteristics, are more vulnerable to the negative effects of social media and more likely to develop body dysmorphic disorder.